2023
DOI: 10.1523/eneuro.0296-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Functional Connectome Topology in Adolescence: Evidence from Topological Data Analysis

Abstract: Adolescence is a crucial developmental period in terms of behavior and mental health. Therefore, understanding how the brain develops during this stage is a fundamental challenge for neuroscience. Recent studies have modeled the brain as a network or connectome, mainly applying measures from graph theory, showing a change in its functional organization, such as an increase in its segregation and integration. Topological Data Analysis (TDA) complements such modeling by extracting high-dimensional features acros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Recent neuroimaging studies have shown that the organization of functional brain networks plays a crucial role in cognitive processing (e.g., Barabási et al, 2023; Bassett & Bullmore, 2017). Many previous studies have used graph theory or network science as an analytical framework to infer global and local properties of brain network topology and to investigate the association of brain network topology with cognitive abilities (for individual studies, see Gracia-Tabuenca et al, 2023; Kristanto et al, 2023; Van Den Heuvel et al, 2009; for a review, see Barabási et al, 2023; Blanken et al, 2021). Network science provides a comprehensive and integrated approach to understanding brain function by considering the complex interactions among multiple brain regions, and thus, the use of network science to study how the brain is organized to control cognitive processing is growing.…”
Section: Introductionmentioning
confidence: 99%
“…Recent neuroimaging studies have shown that the organization of functional brain networks plays a crucial role in cognitive processing (e.g., Barabási et al, 2023; Bassett & Bullmore, 2017). Many previous studies have used graph theory or network science as an analytical framework to infer global and local properties of brain network topology and to investigate the association of brain network topology with cognitive abilities (for individual studies, see Gracia-Tabuenca et al, 2023; Kristanto et al, 2023; Van Den Heuvel et al, 2009; for a review, see Barabási et al, 2023; Blanken et al, 2021). Network science provides a comprehensive and integrated approach to understanding brain function by considering the complex interactions among multiple brain regions, and thus, the use of network science to study how the brain is organized to control cognitive processing is growing.…”
Section: Introductionmentioning
confidence: 99%